New distribution record of cryptotermes brevis (isoptera, kalotermitidae) in argentina (2014)
The first record of the West Indian drywood termite Cryptotermes brevis  (Walker, 1853) in the city of Corrientes (Argentina) is reported. Several C. brevis  colonies were detected inside a local deposit, from wooden crates used for carrying fresh fruits. The observed damage consisted of small rounded holes, partially hollowed wood pieces and presence of debris. The importance of weather factors and the type of material of vegetable and fruit containers in the colonization and dispersion of C. brevis  in this region of Argentina are discussed. Illustrations of soldiers and reproductive C. brevis , and an updated map of the distribution of this termite in Argentina are given.Nuevo registro de distribución de Cryptotermes brevis (Isoptera, Kalotermitidae) en Argentina Se presenta el primer registro de Cryptotermes brevis  (Walker, 1853) en la ciudad de Corrientes (Argentina). Se detectaron varias colonias de esta termita dentro de un edificio en contenedores de madera empleados para el transporte de fruta fresca. Los daños observados consistieron en orificios redondos, piezas de madera parcialmente excavadas y presencia de debris fecales. Se discute la importancia de factores climatológicos y del tipo de material de contenedores de fruta, en la colonización y dispersión de C. brevis  en esta región de Argentina. Se presentan ilustraciones de soldados y reproductores de C. brevis  y un mapa actualizado de la distribución de esta termita en Argentina